1978
DOI: 10.1073/pnas.75.12.6253
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free ring expansion of penicillin N to deacetoxycephalosporin C by Cephalosporium acremonium CW-19 and its mutants.

Abstract: To examine microbiological ring expansion of penicillin N to a cephalosporin, we obtained five mutants of Cephalosporium acremonium blocked in beta-lactam antibiotic biosynthesis from 2500 survivors of mutagenesis. In submerged fermentation, mutants M-0198, M-0199, and M-2351 produced no beta-lactam antibiotic (type A), whereas mutants M-1443 and M-1836 formed penicillin N but not cephalosporin C (type B). Cell-free extracts of type A mutants converted penicillin N to a cephalosporin; those of type B mutants d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…I taught Jack (known as "Acid Jack" by the students at MIT) microbiology and he taught me chemistry. The ring expansion reaction was confirmed by Japanese Visiting Scientists Masaru Yoshida, Toshio Konomi, and Yosuke Sawada along with Kohsaka and Hunt and members of Baldwin's group (75). Type A mutants produced no penicillin N or cephalosporin and their cell-free extracts converted penicillin N to deacetoxycephalosporin C (DAOC); these were obviously blocked before penicillin N early in the pathway.…”
Section: The β-Lactam Antibioticsmentioning
confidence: 88%
“…I taught Jack (known as "Acid Jack" by the students at MIT) microbiology and he taught me chemistry. The ring expansion reaction was confirmed by Japanese Visiting Scientists Masaru Yoshida, Toshio Konomi, and Yosuke Sawada along with Kohsaka and Hunt and members of Baldwin's group (75). Type A mutants produced no penicillin N or cephalosporin and their cell-free extracts converted penicillin N to deacetoxycephalosporin C (DAOC); these were obviously blocked before penicillin N early in the pathway.…”
Section: The β-Lactam Antibioticsmentioning
confidence: 88%
“…The cephalosporin producing organisms that have been most studied to date (c. acremonium and S. clavu/igerus) both also produce penicillin N. There are, therefore, two possible routes from the tripeptide to the cephem products, one by direct cyclisation of the tripeptide, the other by enzymic ring expansion of penicillin N. The first evidence that penicillin N could be converted enzymically to a cephalosporin was provided by KOHSAKA and DEMAIN (289) who demonstrated that lysed protoplasts of C. acremonium could convert penicillin N to another antibiotic or antibiotics which were destroyed by cephalosporinase but not by penicillinase. The product of this cell-free enzymic reaction was characterised as deacetoxycephalosporin C (297) by YOSHIDA et al (290). These authors also showed that cell-free …”
Section: Coohmentioning
confidence: 95%
“…Yoshida et al (130) have ascertained this conversion by the use of Cephalosporium mutants blocked in the synthesis of the ,8-lactam antibiot ics. Using thin-layer chromatography and paper electrophoresis, they also identifi ed the product of the cell-free reaction as deacetoxycephalosporin C. The precise mechanism of conversion of penam ring into cephem is, how ever, still unknown.…”
Section: Biosynthesismentioning
confidence: 99%